Upaya Pencegahan Politik Uang dan Hoaks Dalam Pemilu di Indonesia: Analisis Yuridis dan Implementasinya - Priyantoro, Lucky; Triadi, Irwan (Media Hukum Indonesia (MHI), 2024)
Democratic government in Indonesia has been a rule of law since the Second Amendment to the 1945 Constitution, and elections have become an important tool for encouraging democracy and the transfer of power. However, money politics has become a common phenomenon that causes unfit leaders and sabotages the country's political paradigm. The rise of hoaxes, which are created, replicated and disseminated through public channels, is a problem that needs to be addressed. This research examines election political campaigns in Indonesia, laws and regulations governing the receipt of money in politics, and efforts to prevent hoaxes. This research will use a normative juridical research design with a literature review as the main data source. Researchers will be able to fully understand the Efforts and Implementation of Preventing Hoax Money Politics in the Elections in Indonesia that follow using a normative juridical approach. Implementation of statutory tools for bargaining for money politics in regional elections, and criminal sanctions for receiving political money include a prison sentence of 3 years and a maximum fine of 36 million. Media literacy and political literacy are important preventive measures against hoaxes, and the internet presents challenges such as a lack of online discourse and scientific verification in discussions.